2017
DOI: 10.31351/vol26iss2pp56-65
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Barriers Towards Breast Cancer Health Education Among Iraqi Community Pharmacists

Abstract: With the increasing prevalence of breast cancer among female internationally, occupies about 25% of all cases of cancer, with a measured 1.57 million up to date cases in 2012. Breast cancer has turn a most warning to health of female in Iraq, where it is the major cause of death among women after cardiovascular diseases, with a mortality rate of 23% related cancer. Recently there is a crucial requirement to include community pharmacists in health elevation activities to support awareness and early diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This is not surprising as some studies have also reported lack of education on cancer as one of the reasons for inadequate knowledge of cancer. 11,22 From these findings, it can be concluded that lack of knowledge on cancer, signs and symptoms, risk factors, and cancer screening tests among Ghanaian community pharmacists is due to lack of education or insufficient undergraduate education. This current study shows that a brief, tailor-made educational module was associated with an improved knowledge of community pharmacists on cancer, signs and symptoms, risk factors, and cancer screening tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not surprising as some studies have also reported lack of education on cancer as one of the reasons for inadequate knowledge of cancer. 11,22 From these findings, it can be concluded that lack of knowledge on cancer, signs and symptoms, risk factors, and cancer screening tests among Ghanaian community pharmacists is due to lack of education or insufficient undergraduate education. This current study shows that a brief, tailor-made educational module was associated with an improved knowledge of community pharmacists on cancer, signs and symptoms, risk factors, and cancer screening tests.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as some studies have also reported lack of education on cancer as one of the reasons for inadequate knowledge of cancer. 11,22 From these findings, it can be concluded that lack of knowledge on cancer, signs and symptoms, risk factors, and cancer screening tests among Ghanaian community pharmacists is due to lack of education or insufficient undergraduate education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation